To find the radius of the circle, we need to rearrange the equation of the circle into standard form: (x - h)^2 + (y - k)^2 = r^2.
Given equation: y^2 + x^2 - 14x - 8y + 56 = 0
Rearranging the equation: x^2 - 14x + y^2 - 8y = -56
Completing the square for x: (x^2 - 14x + 49) + y^2 - 8y = -56 + 49
Completing the square for y: (x^2 - 14x + 49) + (y^2 - 8y + 16) = -56 + 49 + 16
Rewriting the equation: (x - 7)^2 + (y - 4)^2 = 9
Comparing this equation with the standard form, we can see that the radius (r) is equal to 3.
Therefore, the correct answer is: 3.
The radius of a circle y2+x2-14x-8y+56=0 is
Question 5 Select one:
-4
-3
3
4
1 answer